What Determines the Implementation of IMF-Supported Programs? - Mourmouras, Alex (IMF Working Papers; Working Paper ;, 2003)
This paper assesses the implementation of IMF-supported programs using measures of program interruptions, compliance with conditionality, and the share of committed funds disbursed. The econometric model allows an evaluation of the importance for program implementation of political conditions in borrowing countries, IMF effort, conditionality, as well as initial and external conditions. The paper concludes that program implementation depends primarily on borrowing countries' domestic political economy. Strong special interests, political instability, inefficient bureaucracies, lack of political cohesion, and ethno-linguistic divisions weaken program implementation. IMF effort, the extent and structure of conditionality, and initial and external conditions do not materially influence program prospects.